Peningkatan Pengetahuan Pemasaran UMKM melalui Pelatihan Perbaikan Kemasan dan Penjualan di Marketplace di Desa Cibadak, Kecamatan Ciampea, Bogor - Jono Mintarto Munandar; Hardiana Widyastuti; Nisa Zahra; Nesti Handayani (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are one of the drivers of the national economy, which, in its journey, has faced various challenges, one of which is related to marketing. Formulating the right marketing strategy is a crucial factor in being able to face challenges and help increase sales of MSME products, including through packaging and digital marketing. This activity aims to improve the performance of MSMEs in Cibadak Village through 1) The process of changing knowledge (cognitive) related to aspects of packaging and digital marketing through the marketplace and 2) The process of changing behavior (psychomotor) related to aspects of packaging and digital marketing through the marketplace. This activity was carried out in Cibadak Village, Ciampea District, West Java Province, between 1 October and 3 November 2022. Consisting of 2 training sessions and two site visits. This activity resulted in changes in the knowledge and behavior of MSME actors in Cibadak Village. Changes in knowledge are illustrated by the results of the pre-test and post-test, which show that overall, there is an increase in knowledge regarding packaging (45.2%) and digital marketing (11.8%) of products processed by MSMEs in Cibadak Village. Then, changes in behavior are marked by changes in previously simple and unhealthy packaging to more attractive and healthy packaging. Apart from packaging, there has also been a change in marketing patterns, from previously only offline, now trying to use digital marketing using marketplace facilities.